Accurate diagnosis of isolated iliac vein thrombosis in third trimester pregnancy with clues on great saphenous vein reflux: a case report and review of literature - Zhanghong Wei; Jingzhi Li; Lijun Liang; Hui Luo (BMC, 2023)
Abstract Background Pregnancy is known to be a risk factor for venous thromboembolism (VTE). We report the case of a pregnant patient with difficult to diagnose iliac vein thrombosis, establishing a definite diagnosis by clues of great saphenous vein reflux. Case presentation A 37-year-old G1P0 woman at 35 weeks of assisted twin gestation presented with a complaint of persistent left lower limb edema and tenderness. A vascular ultrasound was used to examine the bilateral lower limb. Doppler of left lower extremity revealed continuous great saphenous vein reflux. Right saphenofemoral veins demonstrated venous stasis and no reflux. Unilateral continuous great saphenous vein reflux suggested left iliac veins obstruction or extrinsic compression. Anterograde venography showed a completely occlusive filling defect of the left external iliac vein, which is the definitive diagnosis of acute deep venous thrombosis. The patient underwent a cesarean delivery following inferior vena cava filter (IVCF) placement, and no signs of deep venous thrombosis (DVT) or pulmonary embolism (PE) were reported after delivery. Conclusion In pregnant women with suspected deep vein thrombosis, it is imperative to assess the presence of unilateral continuous great saphenous vein reflux.